EFL Teachers' Knowledge and Challenges in Fostering Language Learner Autonomy in Indonesian Context - Muh. Azhar Kholidi; Siti Maftuhah Damio (Nusantara Science and Technology Proceedings, 2024)
The rapid advancement of technology in language teaching has led teachers to shift their teaching-learning methods in their classrooms. This change undoubtedly demands that students be more autonomous outside and inside the classroom. Thus, the present study sought the EFL teachers' knowledge on promoting language learner autonomy (LLA) in their teaching-learning. Employing a survey study, a total of 70 EFL teachers in senior high school levels across Mataram, Indonesia, were involved in this study through a given questionnaire. The data were analyzed using SPSS software version 25 to find out the questionnaire's mean, frequency, and percentage through descriptive statistics analysis. The findings depicted that EFL teachers' knowledge of fostering LLA is positive. They perceived LLA as an essential concept for English language teaching and learning. Moreover, the EFL teachers' knowledge was rated at a moderate level. Nevertheless, many EFL teachers encountered some challenges in developing LLA. The challenges were related to the learners and the teachers, such as the lack of experience in LLA and the EFL teachers' lack of strategies for promoting LLA in their classrooms. The findings suggested that EFL teachers should consistently be able to enact language learner autonomy concepts in their classrooms to support their students to become more autonomous language learners outside the school, both in the EFL and ESL classroom settings.